A study of the effect of plasma treatment on the interfacial properties of carbon ﬁbre–thermoplastic composites - Montes-Morán, M. A. (2005)
GRICES/CSIC Program - Proc.423/ESPANHA. Fundação para a Ciência e Tecnologia. POCTI Program. EU project G1RD-CT-2002-00747. MCYT/FEDER - Pproject MAT2002-00341.